The Emerald international handbook of activist criminology - Canning, Victoria; Martin, Greg; Tombs, Steve; Agozino, Onwubiko (Emerald Publishing Limited, 2023)
Although intervention and campaigning have long been integral to critical criminology, in recent years, criminal justice activism has taken new directions and gathered momentum, especially with the advent of digital technologies and social media. These have made it easier than ever for ordinary citizens and professional journalists alike to comment on perceived injustices and potentially intervene in formal criminal justice processes. The Emerald International Handbook of Activist Criminology examines the history of both recent and more established justice campaigns and interventions. Spanning contributions from activists, activist academics, and practitioners from five continents, chapters address a range of criminological perspectives that engage in questions of effecting change through activism. Contributors also consider prominent international issues including feminist criminology, juvenile justice, migrant rights, corporate and state crime, indigenous rights, green/environmental criminology, sentencing and wrongful conviction, the harms of prisons, corrections and abolitionism, and justice for victim/survivors of harm and crime. Collectively, The Emerald International Handbook of Activist Criminology explores the contemporary terrain around new and emergent issues and forms of activism, and offers cutting edge conceptualizations of the methodological and practical applications of activist engagement, solidarity, and resistance.
Keywords: Criminology -- Social aspects.; Activism.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books